2009
DOI: 10.1007/s00540-009-0777-9
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine-induced cerebral hypoperfusion exacerbates ischemic brain injury in rats

Abstract: Hypertension following the administration of high-dose dexmedetomidine is associated with cerebral hypoperfusion and the exacerbation of ischemic brain injury, possibly through alpha-2-induced cerebral vasoconstriction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…In the developing mouse brain, dose-dependent neuroprotection with dexmedetomidine and clonidine was found [66] . Some studies, however, have shown that dexmedetomidine and clonidine induce cerebral hypoperfusion and neurotoxicity in small-animal stroke models [67] . Dean et al [68] showed a complex dose-dependent response to clonidine with low doses, but not high doses, being neuroprotective after hypoxic brain injury in preterm fetal sheep.…”
Section: Discussionmentioning
confidence: 99%
“…In the developing mouse brain, dose-dependent neuroprotection with dexmedetomidine and clonidine was found [66] . Some studies, however, have shown that dexmedetomidine and clonidine induce cerebral hypoperfusion and neurotoxicity in small-animal stroke models [67] . Dean et al [68] showed a complex dose-dependent response to clonidine with low doses, but not high doses, being neuroprotective after hypoxic brain injury in preterm fetal sheep.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine activates all three sub-types of a 2 adrenoceptors, which are present in high concentrations in vascular smooth muscle, as well as in key arousal areas of the central nervous system, such as the locus ceruleus [6]. The activation of a 2A receptors by dexmedetomidine exerts neuroprotective effects [7][8][9], while the activation of a 2B receptors constricts cerebral vessels and decreases cerebral blood flow (CBF) [6,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its potential benefits, dexmedetomidine can have deleterious effects on cardiovascular and cerebrovascular functions which mandate close hemodynamic monitoring during infusion. Nakano recently reported that dexmedetomidine-induced cerebral hypoperfusion exacerbated ischemic brain injury in rats [28]. Hypotension was observed in 10 of 39 (26%) neurosurgical patients treated with dexmedetomidine infusions for sedation during intubation in the ICU [21].…”
Section: Discussionmentioning
confidence: 99%